Strategi Pemasaran Poli Bedah Estetik Bali Royal Hospital (Bros) Denpasar - Nugraha, Deity Indrayati (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2017)
This study aims to create a good marketing strategy to determine the problems faced so it is expected that in the end the number of visits to the aesthetic surgery surgery BROS Denpasar has increased. This research uses qualitative method with observation, and in-depth interview. From the product-price mix, there are several strategies, namely by providing variations of products or additional services, buying aesthetic surgical instruments with the latest technology, and can also lower the rates of aesthetic surgery services. For the price place mix, the strategy is to move the esthetic surgical poly to a more private room. The strategy for people promotion mix, by increasing cooperation with other medical tourism agents, altering the contents of the BROS website so as to highlight aesthetic surgery services, and more actively for the promotion of aesthetic surgery services in social media. The strategy of the people-physical evolution mix, which is to provide short courses of foreign languages for doctors and nurses, to find a permanent plastic surgeon, and to place a permanent nurse for plastic surgery. Process-promotion strategy, ie by reducing intermediaries or cutting the flow of aesthetic surgical service process in cooperation with foreign agents (ABA).